Gender differences in patients with obesity hypoventilation syndrome. (18th March 2016) - BaHammam, Ahmed S.; Pandi‐Perumal, Seithikurippu R.; Piper, Amanda; Bahammam, Salman A.; Almeneessier, Aljohara S.; Olaish, Awad H.; Javaheri, Shahrokh
Summary: The role of gender and menopause in obstructive sleep apnoea is well known; however, no study has reported the impact of gender on the clinical presentation and the nocturnal respiratory events in patients with obesity hypoventilation syndrome. Therefore, this study prospectively evaluated differences in the clinical characteristics of women and men with obesity hypoventilation syndrome in a large cohort of patients with obstructive sleep apnoea. During the study period, a total of 1973 patients were referred to the sleep clinic with clinical suspicion of obstructive sleep apnoea. All patients underwent overnight polysomnography, during which time spirometry, arterial blood samples and thyroid tests were routinely obtained. Among 1973 consecutive patients, 1693 (617 women) were diagnosed with obstructive sleep apnoea, among whom 144 suffered from obesity hypoventilation syndrome (96 women). The prevalence of obesity hypoventilation syndrome among women and men was 15.6% and 4.5%, respectively ( P < 0.001). Women with obesity hypoventilation syndrome were significantly older than men with obesity hypoventilation syndrome (61.5 ± 11.9 years versus 49.1 ± 12.5 years, P < 0.001). Although there were no significant differences between genders regarding symptoms, body mass index, spirometric data or daytime PaCO2, women with obesity hypoventilation syndrome suffered significantly more from hypertension, diabetes and hypothyroidism. The prevalence of obesity hypoventilation syndrome was higher in post‐menopausal (21%) compared with pre‐menopausal (5.3%) women ( P < 0001). HCO3 and duration of SpO2 <90% were the only independent predictors of obesity hypoventilation syndrome. In conclusion, this study reported that among subjects referred to the sleep disorders clinic for evaluation of obstructive sleep apnoea, obesity hypoventilation syndrome is more prevalent in women than men, and that women with obesity hypoventilation syndrome suffer from significantly more co‐morbidities. Post‐menopausal women with obstructive sleep apnoea have the highest prevalence of obesity hypoventilation syndrome.